Efficacy and safety of induction therapy with calcineurin inhibitors followed by vedolizumab maintenance in 71 patients with severe steroid‐refractory ulcerative colitis. Issue 6 (25th December 2019) - Ollech, Jacob E.; Dwadasi, Sujaata; Rai, Victoria; Peleg, Noam; Normatov, Inessa; Israel, Amanda; Sossenheimer, Philip H.; Christensen, Britt; Pekow, Joel; Dalal, Sushila R.; Sakuraba, Atsushi; Cohen, Russell D.; et al.
Summary: Background: Following induction therapy with a calcineurin inhibitor (CNI) in severe ulcerative colitis, transitioning to vedolizumab as maintenance therapy could be an option. Aim: To report on the largest cohort of patients successfully induced with CNIs who were transitioned to vedolizumab maintenance therapy. Methods: This is a retrospective observational study of adult patients with severe steroid‐refractory ulcerative colitis. Patients were included if they were induced with a CNI followed by maintenance therapy with vedolizumab between January 2014 and December 2018. The primary endpoint was colectomy‐free survival. Secondary endpoints included survival without vedolizumab discontinuation as well as clinical, steroid‐free and biochemical remission at week 14. Results: A total of 71 patients (59% male) were treated with vedolizumab after induction therapy with CNIs for severe steroid‐refractory colitis. Patients were followed for a median time of 25 months (IQR 16‐36). Colectomy‐free survival rates from vedolizumab initiation were 93% at 3 months, 67% at 1 year and 55% at 2 years. At the end of induction with vedolizumab at week 14, 50% of patients were in clinical remission, and 62% of patients had a normal CRP. At 1 and 2 years following vedolizumab initiation, 43% and 28% of patients were still on vedolizumab respectively. Vedolizumab was dose escalated to infusions every 4 weeks in 44% of patients. The median time to dose escalation was 5.6 months (IQR 4.1‐8.2). No serious adverse events were recorded in our patient cohort. Conclusions: Transitioning to vedolizumab following induction of remission with CNIs is effective and safe.